2019
DOI: 10.1038/s41467-019-13311-1
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring heterogeneities in high-entropy alloys to promote strength–ductility synergy

Abstract: Conventional alloys are usually based on a single host metal. Recent high-entropy alloys (HEAs), in contrast, employ multiple principal elements. The strength of HEAs is considerably higher than traditional solid solutions, as the many constituents lead to a rugged energy landscape that increases the resistance to dislocation motion, which can also be retarded by other heterogeneities. The wide variety of nanostructured heterogeneities in HEAs, including those generated on the fly during tensile straining, als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 384 publications
(94 citation statements)
references
References 96 publications
2
82
0
Order By: Relevance
“…There have been several important HEA studies reporting breakthroughs in strength-ductility synergy at cryogenic and room temperatures 7 , 20 22 , 40 ; however, none of them have addressed the high temperature mechanical properties of these HEAs. Therefore, this article uniquely addresses the issue of high temperature tensile strength of HEAs, especially the HESA in the HT-2 condition has performed exceptionally well comparing reported HEAs and advanced superalloys, Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several important HEA studies reporting breakthroughs in strength-ductility synergy at cryogenic and room temperatures 7 , 20 22 , 40 ; however, none of them have addressed the high temperature mechanical properties of these HEAs. Therefore, this article uniquely addresses the issue of high temperature tensile strength of HEAs, especially the HESA in the HT-2 condition has performed exceptionally well comparing reported HEAs and advanced superalloys, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In conventional precipitation strengthened superalloys, precipitation of coherent Ni 3 (Al, Ti) L1 2 structured phase in FCC matrix can provide effective strengthening 19 . Recent studies have shown that coherent L1 2 phase could also be an effective strengthener in HEAs 11 , 20 22 , for example, L1 2 precipitation in Al 7 (Fe, Co, Ni) 86 Ti 7 resulted a combination of high tensile yield strength (1,028 MPa) with large elongation (47.8%) at room temperature 20 . However, the elevated temperature tensile strength of HEA could be limited by insufficient fractions and relatively low solvus of strengthening phases in HEAs 11 .…”
Section: Introductionmentioning
confidence: 99%
“…In advanced high strength steels for structural applications, to pursue the superior (σ y , ε u ) combination causes long concern [1][2][3][4][5][6][7][8], where σ y is the yield strength and ε u is the tensile uniform strain. So far, the real challenge lies in low ε u particularly at high and even ultrahigh σ y [1][2][3], typical of the (σ y , ε u ) trade-off.…”
mentioning
confidence: 99%
“…So far, the real challenge lies in low ε u particularly at high and even ultrahigh σ y [1][2][3], typical of the (σ y , ε u ) trade-off. The crux of the problem is inadequate strain hardening, which can no longer keep up with high flow stress to circumvent plastic instability [6][7][8], i.e. necking via strain localization, as predicted by the Considerè criterion.…”
mentioning
confidence: 99%
See 1 more Smart Citation